Environmental Health Risk Assessment (EHRA) of Air Pollution from Transportation Activities at Bus Terminals in Medan City - Restu Auliani; Erba Kalto Manik (CV. Get Press Indonesia, 2026)
Air pollution from transportation activities at bus terminals poses significant environmental health risks, particularly in densely populated urban areas. This study aims to assess the health risks associated with exposure to air pollutants among individuals working at bus terminals in Medan City, Indonesia. A quantitative descriptive approach using Environmental Health Risk Assessment (EHRA) was applied. Data were collected through direct measurements of carbon monoxide (CO), nitrogen dioxide (NO₂), and particulate matter (PM2.5), as well as interviews to determine exposure duration, frequency, and body weight. The study involved 60 respondents, including traders, drivers, and terminal officers. Risk characterization was conducted using the Risk Quotient (RQ). The results indicated that the concentrations of CO and PM2.5 exceeded WHO air quality standards during peak hours. The RQ values for a majority of respondents were greater than 1, indicating potential non-carcinogenic health risks. The highest risk was observed among traders due to prolonged exposure duration. These findings highlight the urgent need for emission control strategies, improved environmental management, and health protection measures for vulnerable populations. In conclusion, EHRA is an effective tool to evaluate environmental health risks in transportation hubs.